2015
DOI: 10.1111/bjd.14207
|View full text |Cite
|
Sign up to set email alerts
|

The first trial of CIM331, a humanized antihuman interleukin-31 receptor A antibody, in healthy volunteers and patients with atopic dermatitis to evaluate safety, tolerability and pharmacokinetics of a single dose in a randomized, double-blind, placebo-co

Abstract: SummaryBackground The cytokine interleukin-31 (IL-31) is considered to be responsible for the development of pruritus in humans. At present, no available evidence has been provided on the safety and efficacy of blocking the IL-31 signal in humans for the amelioration of pruritus in atopic dermatitis (AD). CIM331 is a humanized antihuman IL-31 receptor A (IL-31RA) monoclonal antibody, which binds to IL-31RA to inhibit subsequent IL-31 signalling. Objectives To assess the tolerability, safety, pharmacokinetics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
122
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(128 citation statements)
references
References 30 publications
1
122
0
5
Order By: Relevance
“…The first phase I study revealed a statistically significant 50% reduction in itch, assessed by the pruritus visual analogue scale, 4 weeks after initiation of treatment compared to the placebo group (20% reduction) [57]. Moreover, nemolizumab decreased sleep disturbance and use of topical hydrocortisone.…”
Section: Nemolizumabmentioning
confidence: 99%
“…The first phase I study revealed a statistically significant 50% reduction in itch, assessed by the pruritus visual analogue scale, 4 weeks after initiation of treatment compared to the placebo group (20% reduction) [57]. Moreover, nemolizumab decreased sleep disturbance and use of topical hydrocortisone.…”
Section: Nemolizumabmentioning
confidence: 99%
“…45,114 In addition, the anti-IL-31 receptor A antibody nemolizumab successfully resolves atopic itch. 57,115 Despite the safety and the considerable effectiveness of these biologics, there still exists high and low responders. This fact reiterates the heterogeneity of AD.…”
Section: Chemokine S In Atopic De Rmatitismentioning
confidence: 99%
“…По данным Nobbe и соавт., в воспалительном инфильтрате биоптатов кожи больных АД определяется повышенный уровень ИЛ-31 по сравнению со здоровой кожей и кожей больных другими воспалительными заболеваниями [98]. Экспериментальными исследованиями отмечен значи-мый вклад ИЛ-31 в индукцию кожного зуда у больных АД [99,100]. В работе Dillon и соавт., у трансгенных мышей на фоне гиперэкспрессии ИЛ-31 развивались кожные высыпания, сходные с таковыми при АД и пруриго [101].…”
Section: антицитокиновая терапияunclassified